PENGARUH METODE DAN SUHU BLANCHING TERHADAP PERSENYAWAAN SERAT BATANG PISANG SEBAGAI BAHAN BAKU PEMBUATAN ARES: The Effect of Methods and Temperature of Blanching Treatment on Fiber Compounds of Banana Stem as Raw Material of Ares - Arin Tria Agustin; Mohammad Abbas Zaini; Dody Handito (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2020)
ABSTRACT This study aims to determine the combination of methods and temperature of blanching treatment on crude fiber content, total dietary fiber, insoluble dietary fiber content and soluble dietary fiber content of banana steam as raw material of ares. The experimental design used in this study was Completely Randomized Block Design (CRBD) factorial with six treatments and three repetitions to obtain 18 samples. The combination of treatment consisted of M1T1 (steaming 75°C), M1T2 (steaming 85°C), M2T1 (boiling 75°C), M2T2 (boiling 85°C), M3T1 (boiling with Na2S2O5 0,1% solution 75°C), M3T2 (boiling with Na2S2O5 0,1% solution 85°C). The result of this study were analyzed using ANOVA (Analysis of Variance) diversity analysis at 5% level using Co-Stat Software. The result that had significant differences were continued to analyzed using Honestly Significant Different Test (BNJ) at 5% real level. The result showed that the combination of methods and temperature of blanching treatment did have a significant effect oncrude fiber content, insoluble dietary fiber content, soluble dietary fiber content dan total dietary fiber content. The best result of banana stem based on nutritional quality of fiber was steaming 75°C treatment with crude fiber content 0.5413%, total dietary fiber content 22.059%, insoluble dietary fiber content 19.978% and soluble dietary fiber content 2.081%. The best result of Ares based on nutritional quality of fiber was steaming 75°C treatment with crude fiber content 4,321%, total dietary fiber content 46,057%, insoluble dietary fiber content 42,112% and soluble dietary fiber content 3,945%. Keywords: ares, banana stem, blanching, crude fiber, dietary fiber. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi metode dan suhu blanching terhadap kadar serat kasar, kadar serat pangan total, kadar serat pangan tidak larut dan kadar serat pangan larut batang pisang sebagai bahan baku pembuatan Ares. Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok (RAK) pola faktorial dengan enam kombinasi perlakuan dan tiga kali pengulangan sehingga diperoleh 18 sampel. Kombinasi perlakuan terdiri dari M1T1 (pengukusan 75°C), M1T2 (pengukusan 85°C), M2T1 (perebusan 75°C), M2T2 (perebusan 85°C), M3T1 (perebusan dengan larutan Na2S2O5 0,1% 75°C), M3T2 (perebusan dengan larutan Na2S2O5 0,1% 85°C). Data hasil pengamatan diuji dengan analisis keragaman pada taraf nyata 5% menggunakan software Co-Stat. Apabila terdapat perbedaan nyata, maka dilakukan uji lanjut Beda Nyata Jujur (BNJ) pada taraf 5%. Hasil terbaik batang pisang berdasarkan mutu nutrisi serat yaitu perlakuan pengukusan 75°C dengan kadar serat kasar 0,5413%, kadar serat pangan tidak larut 19,978%, kadar serat pangan larut 2,081% dan kadar serat pangan total 22,059%. Hasil terbaik pada ares berdasarkan mutu nutrisi serat adalah perlakuan pengukusan pada suhu 75°C dengan kadar serat kasar 4,321%, serat pangan total 46,057%, serat pangan tidak larut 42,112% dan serat pangan larut 3,945%. Kata kunci: Ares, batang pisang, blanching, serat kasar, serat pangan.